Microwave-Assisted Synthesis of Quinazolines and Quinazolinones: An Overview - Mohammadkhani, Leyla; Heravi, Majid M. (Frontiers in Chemistry, 2020)
Microwave irradiation (MWI), as a unique, effective, sustainable, more economic, and greener source of energy compared to conventional heating, is applied in different organic transformations to result in the rapid formation of desired compounds due to thermal/kinetic effects. In this review, we try to underscore the applications of microwave irradiation (MWI) in the synthesis of quinazoline and quinazolinone derivatives that have been achieved and reported on in the last two decades.